Investigating Nasal Anatomy in the Javanese Ethnic Group in Indonesia - Norina Agatri; Gembong Satria Mahardhika; Ahmad Fawzy Mas'ud; Fitranto Arjadi (Poltekkes Kemenkes Tanjung Karang, 2025)
The nasal is a fundamental anatomical feature of humans and serves as a benchmark for beauty ideals. Rhinoplasty is a popular procedure worldwide. References to anatomical elements are crucial when discussing the distinct nasal shapes of each race, particularly in the context of Indonesia. Research is scarce on the nasal morphology of the Javanese ethnic group, resulting in a lack of precise quantitative measurements for their specific nasal form. The study conducted was a cross-sectional investigation with a sample of 50 individuals, consisting of 20 males and 30 females of Javanese ethnicity. The analysis was performed to determine the precise quantities of the three variables under investigation, specifically intercanthal distance, alar width, and base of nasal width. The mean figure at the intercanthal was 2.38 cm, alar base 2.92 cm, and base of nasal width 3.46 cm. The T-test results are significant for the base of nasal width variable at a p-value of 0.002. The acquired data were subsequently juxtaposed with data from various races in Indonesia and other regions, serving as a benchmark for rhinoplasty operations specifically for individuals of Javanese descent in Indonesia. The data reveal a significant gender gap in the Javanese base of nasal width. A study reveals that Javanese nasals are shorter and wider than those of other ethnicities, suggesting that rhinoplasty may be recommended over non-surgical methods.